BRI BANK INFORMATION SYSTEM AUDIT BASED ON CUSTOMER TRANSACTIONS IN MEDAN CITY - Siahaan, yanty faradillah; Rivaldo, Samuel; Mhd. Kabul Maulana; Ramadhani Syahputra Ritonga; lubis, M.Ginda rizky mulia; saragih, Dinda sabrina; Sarah tsabitah; Alfia syahmadina; laia, Tanira; safilla dwi mahirah; Rio Febrian (Cattleya Darmaya Fortuna, 2025)
The era of digital transformation has brought fundamental changes to the banking industry in Indonesia, encouraging banks to optimize information systems to improve service quality and maintain customer loyalty. This study focuses on Bank Rakyat Indonesia (BRI) in Medan City, which is the economic center of North Sumatra with a high level of competition. In this context, information system audits are important to assess the reliability, security, and effectiveness of existing systems. This study aims to evaluate the effect of service quality and customer satisfaction on BRI customer loyalty, as well as to analyze the impact of information technology implementation in improving service quality. The methods used in this study include qualitative and quantitative analysis, with data collection through questionnaires distributed to BRI customers in Medan. The results of the study indicate that there is a significant effect between service quality and customer satisfaction on loyalty. In addition, the digital transformation carried out by BRI, including the implementation of the COBIT and ISO 31000 frameworks, has improved operational efficiency and data security. However, BRI also faces challenges in adapting to changing regulations and strengthening cybersecurity systems. These findings provide valuable insights for BRI management in optimizing more effective information systems and marketing strategies, and emphasize the importance of a customer-centric approach in improving customer experience. Recommendations for BRI include strengthening risk management and utilizing demographic data for more targeted product development, in order to maintain customer loyalty in the increasingly digital era.